2007
DOI: 10.1177/0145721707304171
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Organizational Resources and Supports for Self Management in Primary Care

Abstract: Establishing a comprehensive system of care for people with diabetes is enabled by an infrastructure of organizational resources and supports for self-management in primary care settings. These components of organizational support provide guidance for integrating diabetes self-management services into primary care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 27 publications
4
30
4
Order By: Relevance
“…Use of multidisciplinary care teams was strongly associated with delivery of self-management support, consistent with previous analyses of organizational features of care that predict delivery of such support. 29 In addition, our analyses suggest that improving delivery of self-management support may require unique activities for individual chronic conditions, as there was little correlation detected between self-management support scores for these conditions within medical groups.…”
Section: Discussionmentioning
confidence: 78%
“…Use of multidisciplinary care teams was strongly associated with delivery of self-management support, consistent with previous analyses of organizational features of care that predict delivery of such support. 29 In addition, our analyses suggest that improving delivery of self-management support may require unique activities for individual chronic conditions, as there was little correlation detected between self-management support scores for these conditions within medical groups.…”
Section: Discussionmentioning
confidence: 78%
“…48,53 For example, the Enhancing Practice, Improving Care study found that practice facilitation using a continuous quality improvement approach was effective at improving measures of diabetes care. 51 Likewise, Shetty et al 55 examined the components of organizational support for SMS in primary care practices. These researchers found 8 essential elements of organizational support, including ongoing quality "The team already has many of the attitudes and skills (follow up calls to check on action plan progress, etc.)…”
Section: Repelling Factors Pushing Against Sms Transformationmentioning
confidence: 99%
“…The programs and their achievements are described in detail on the Diabetes Initiative Web site (http://diabetesinitiative.org) and in numerous journal articles, [10][11][12][13][14][15][16] including a special supplement to The Diabetes Educator. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] Six of the 14 projects funded through this initiative focused on improving self-management supports in primary care settings. Their projects began with a 15-month planning phase, during which they tested innovative approaches to reaching and engaging their respective patient populations in self-management.…”
Section: Program Description Implementation Settingsmentioning
confidence: 99%